Revitalization of Internal Audit in The Framework of Developing a Risk Management Program as an Early Warning System: Case Study “Carrefour Indonesia” - IRSAN, Muhammad Syah (PT Keberlanjutan Strategis Indonesia, 2024)
This thesis discusses the revitalization of the main duties and functions of internal audit regarding the application of the Risk Management Program at